Administrative Control and Employees’ Productivity in Rivers State Ministry of Education, 2015-2022 - OLUMBA Enyichukwu; NWANKWO Evans Onuabuchi; LUKE, Mkpaofiek Grace; ECHEONWU, Macdonald Silas; HARUNA, Monday Ocheja; EMENONYE, Henry Nkem; BARIKOR ThankGod (Zien Journals, 2023)
Efficient administrative management is crucial for enhancing worker productivity in the public sector in Nigeria.Over the years, the Nigerian public sector has seen a decrease in productivity, effectiveness, efficiency, and commitment to duty. This study examined the impact of administrative control on the efficiency of employees in the Rivers State Ministry of Education.The study was guided by three research queries and their corresponding research objectives.The study is based on the Goal-Setting Theory.The study used a survey methodology.The study used a simple random sampling technique to choose a sample size of 200 individuals.The research data were acquired from two primary sources: primary and secondary sources.The primary data were assessed using fundamental statistical metrics, including percentages, tables, mean, and standard deviation. The secondary data, however, were subjected to content analysis for analysis.The data analysis revealed a significant association between administrative control and workers' productivity at the Rivers State Ministry of Education. The research revealed that factors such as administrative control, work environment, technology, workload, and work-life balance had a substantial impact on the productivity of workers at the Rivers State Ministry of Education throughout the examined period. The study's findings indicate that personnel in the ministry typically have a good opinion of administrative control. However, there are problems about motivation, workload, job design, and work structure. The research therefore suggests that the Rivers State Ministry of Education should create and enforce policies and processes that enhance efficient administrative oversight, namely in the domains of communication, supervision, and resource allocation.
Keywords: Administration; Employee; Productivity